FAKTOR YANG MEMPENGARUHI OPINI PUBLIK BRITANIA RAYA TERKAIT KEBIJAKAN BREXIT TAHUN 2016 - Pertiwi, Rahmatya Nur Wibi (Global and Policy Journal of International Relations, 2018)
Brexit is a historic phenomenon of Great Britain that wants its country out of the European Union through a referendum policy implemented on June 23, 2016. The results of the referendum Brexit resulted in the decision that the Great Britain must be out of the membership of European Union. The result is entirely left to the people of Great Britain. To analyze the Brexit policy, the use of domestic political level analysis is able to explain the role of domestic actors that influence foreign policy. One of the influential domestic actors in the Brexit policy is British public opinion. In producing Brexit policy, public opinion can‟t be separated from the influence that from within and abroad. It is analyzed using Two-level Games and the theory of decision-making abroad. Brexit dynamics that occurred in 2015-2016 is inseparable from the influence of the political parties of the United Kingdom through the group Vote Leave and Vote Remain. The effects are conveyed through campaign activities conducted directly and through social media. In addition, external factors also influence the public opinion of the United Kingdom about Brexit policy of Euroscepticism. The growing influence of Euroscepticism in the European region has had an impact on people's decisions at the time of the referendum. These influences can be seen from the final result of the referendum deciding to "Leave" or leave the EU membership. Keywords: Brexit, Euroscepticism, Public Opinion, Vote Leave, Vote RemainDOI : https://doi.org/10.33005/jgp.v6i02.1824